2010
DOI: 10.2337/dc09-1974
|View full text |Cite
|
Sign up to set email alerts
|

A High-Protein Diet With Resistance Exercise Training Improves Weight Loss and Body Composition in Overweight and Obese Patients With Type 2 Diabetes

Abstract: OBJECTIVETo evaluate the effects of two low-fat hypocaloric diets differing in the carbohydrate-to-protein ratio, with and without resistance exercise training (RT), on weight loss, body composition, and cardiovascular disease (CVD) risk outcomes in overweight/obese patients with type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 83 men and women with type 2 diabetes (aged 56.1 ± 7.5 years, BMI 35.4 ± 4.6 kg/m2) were randomly assigned to an isocaloric, energy-restricted diet (female subjects 6 MJ/day, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
207
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(231 citation statements)
references
References 24 publications
12
207
2
10
Order By: Relevance
“…As a result of the WL, there are significant improvements in body composition, blood pressure and bio-markers of health. The reduction in body fat mass (kg) and maintenance of lean mass (kg) during energy restriction and WL has been reported previously by other authors and, in part, is related to the protein-enriched composition of the diet (21) . In a recent meta regression, Krieger et al (22) and Clifton et al (23) examined eightyseven short-term studies and found that protein intakes of > 1 .…”
Section: Efficacy Of High-protein Weight Loss Dietssupporting
confidence: 79%
“…As a result of the WL, there are significant improvements in body composition, blood pressure and bio-markers of health. The reduction in body fat mass (kg) and maintenance of lean mass (kg) during energy restriction and WL has been reported previously by other authors and, in part, is related to the protein-enriched composition of the diet (21) . In a recent meta regression, Krieger et al (22) and Clifton et al (23) examined eightyseven short-term studies and found that protein intakes of > 1 .…”
Section: Efficacy Of High-protein Weight Loss Dietssupporting
confidence: 79%
“…For example, some studies showed better glycemic control and insulin sensitivity in patients taking lower levels of carbohydrate23, 24, 25, whereas some others showed no difference26, 27. Conflicting results were also reported by various studies regarding the clinical outcomes in patients having higher or usual protein intake28, 29, 30, 31. Eating plans and nutrition therapy goals should be set collaboratively with individual needs including the patients’ metabolic targets, personal and cultural preferences, literacy and economic capability, as well as their ability and willingness to change16.…”
Section: Discussionmentioning
confidence: 99%
“…However, data interpretation is limited because the majority of studies (10 of 12) included in the glucose analysis were conducted in nondiabetic individuals (24,43). Furthermore, although FFM (skeletal muscle) is the primary site of glucose uptake (6), a direct relation between the quantity of skeletal muscle and glucose tolerance or insulin sensitivity does not follow (61).…”
mentioning
confidence: 99%